Near-Field Angle Measurement of HPM Helical Array Antennas With Its Closed-Loop Control - He, Huaping; Zhang, Heng; Chen, Jie; Sun, Yunfei; Zhang, Qiang (IEEE antennas and wireless propagation letters, 2025)
Measuring the pointing angles of high-power microwave (HPM) helical array antennas presents significant challenges, resulting in a lack of effective angle control schemes in current research. To address this issue, this study proposes a near-field pointing detection method that utilizes dipole antennas for closed-loop control of HPM helical array antenna positioning. The evaluation results obtained via interpolation methods show that the absolute angle error is less than 0.701 ^° . In addition, this work also conducted closed-loop control experiments on HPM helical array antennas based on proportional-integral-derivative control algorithm. Compared to conventional open-loop control systems, the proposed closed-loop control strategy produces a control curve that closely aligns with the theoretical calculation curve, realizing lower steady-state error and improved system robustness.